The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1016/j.envres.2021.112528
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 social distancing compliance mechanisms: UK evidence

Abstract: Non-compliance with social distancing (SD) measures clearly has negative effects on both public health and post-pandemic economic recovery. However, little is as yet known about people's views on and factors influencing their behavioral intentions toward SD measures. This study draws on moral disengagement theory and the norm-activation model to investigate mechanisms that promote or hinder compliance with SD measures. A longitudinal research approach was adopted to compare changes in the main factors over thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 65 publications
0
14
0
Order By: Relevance
“…A number of authors emphasize effective capabilities of a contact tracing/social monitoring/vaccination certification system based on QR codes: rapidity [ 64 ], convenience [ 64 ], epidemiological safety [ 64 , 65 ], effectiveness of ensuring social distance compliance [ 65 ], suitability for telemedicine services [ 66 ], and safety of remote delivery of a patient’s information [ 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…A number of authors emphasize effective capabilities of a contact tracing/social monitoring/vaccination certification system based on QR codes: rapidity [ 64 ], convenience [ 64 ], epidemiological safety [ 64 , 65 ], effectiveness of ensuring social distance compliance [ 65 ], suitability for telemedicine services [ 66 ], and safety of remote delivery of a patient’s information [ 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…Another important way to prevent Omicron is to follow covid-appropriate behaviour by not lowering our guards [1,16]. Individuals should continue to wear a well-fitting mask; open windows to improve No 1 ventilation; avoid poorly ventilated or crowded spaces; keep hands clean; cough or sneeze into a bent elbow or tissue; and get vaccinated when it's their turn (Figure 1).…”
Section: Following Covid-19 Appropriate Behaviourmentioning
confidence: 99%
“…In these instances, the overwhelming presence of the virus might cause many more people to do so. Ahmad (2020, in Wu, Font, & McCamley, 2022 found that individuals' social norms did not necessarily influence how willing people were to adopt recommended measures to inhibit the spread of the virus.…”
Section: Consumer Involvement With Covid-19mentioning
confidence: 99%